Pengaruh Penggunaan Metode Problem Solving Model Polya Terhadap Hasil Belajar Soal Cerita di Sekolah Dasar - Putri, Aprien Rahma; Masniladevi, Masniladevi; Desyandri, Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research aims to determine the effect of using the problem solving method of the Polya model on learning outcomes about the story of the flat-waking class V students of Elementary School 1 North Pariaman. This type of research is Quasi Experimental Type Nonequivalent Control Group Design. The sampling technique used simple random sampling technique with the results of several considerations. The instrument used is a test that is a description test. Data analysis techniques in this study used a prerequisite test in the form of normality and homogeneity tests and hypothesis testing using the t-test. The results showed that there was a significant influence in the use of the problem solving model method on the learning outcomes of the story about the flat-building area of class V SD Cluster 1 North Pariaman. This is evidenced by the results of the t-test with a significance level of 5% obtained tcount = 3.71 > ttable = 1.72. Mathematics learning outcomes obtained by the experimental group were higher than in the control group, indicated by the control group mean = 73.09 and the mean obtained by the experimental group = 87.18.